AN EXPERIMENTAL STUDY OF THE IMPLEMENTATION OF THE SIMULATION TECHNIQUE IN TEACHING SPEAKING - Ana Dewi Saputri; Nanik Supriani (Universitas Sarjanawiyata Tamansiswa, 2018)
Based on observation, the writer identifies the following problems at the seventh grade students of SMPN 1 Samigaluh, the researcher found some factors that influence student’s speaking skill. Thus, this study investigates about the simulation technique in the process teaching-speaking. It used an experimental design involving 32 students in the experimental group and control group. The instrument used was the speaking test (pre-test and post-test) that was given to both groups. The experimental group was given the treatment using simulation technique, while the control group used conventional teaching. Based on the result, the researcher calculate using SPSS that shows sig/p = 0.00. It was smaller than 0.05 (0.02< 0.05), so there is significant difference between students’ speaking skills before and after using simulation to the seventh grade students of SMP N 1 Samigaluh in academic year 2017/2018. Moreover, the simulation technique could help them to improve their speaking ability.